2010
DOI: 10.1159/000300647
|View full text |Cite
|
Sign up to set email alerts
|

When Do Levodopa Motor Fluctuations First Appear in Parkinson’s Disease?

Abstract: Although levodopa provides therapeutic benefit over the entire course of Parkinson’s disease, most patients eventually notice a decline in the duration of benefit from each dose, a phenomenon termed ‘wearing-off’ or ‘end of dose’ deterioration. This is an important indicator that the patient is entering a more complex phase of the disease. Wearing-off has been classically associated with the later stages of Parkinson’s disease, but it is becoming apparent that patients with early disease, presenting as well co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 92 publications
0
75
0
6
Order By: Relevance
“…48,49 Estimates based on some studies indicate that up to 50 % of patients with PD will experience motor fluctuations within the first 2 years of treatments. 50 In addition, the Earlier versus Later Levodopa Therapy in Parkinson Disease (ELLDOPA) study showed that complications can occur within the first year. 51 A recent study designed to evaluate the presence of motor and non-motor fluctuations using a specific questionnaire, the 19- 53,54 Therefore, in the clinic, HRQoL assessments should be easy to use and complement traditional diagnostic evaluations used by physicians.…”
Section: The Clinical Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…48,49 Estimates based on some studies indicate that up to 50 % of patients with PD will experience motor fluctuations within the first 2 years of treatments. 50 In addition, the Earlier versus Later Levodopa Therapy in Parkinson Disease (ELLDOPA) study showed that complications can occur within the first year. 51 A recent study designed to evaluate the presence of motor and non-motor fluctuations using a specific questionnaire, the 19- 53,54 Therefore, in the clinic, HRQoL assessments should be easy to use and complement traditional diagnostic evaluations used by physicians.…”
Section: The Clinical Perspectivementioning
confidence: 99%
“…Wearing-off can appear early in the course of the disease but often is not recognised by patients and doctors. 50 Early morning symptoms, particularly akinesia, have been shown to be correlated with motor aspects of PD and have strongly negative effect on HRQoL as perceived by patients. 46,63,64 The impact of morning akinesia, nocturnal akinesia and biphasic dyskinesias can be effectively Table 2).…”
Section: The Patient's Perspectivementioning
confidence: 99%
“…With time, postural changes and especially gait‐related problems may often be troublesome 3. Dopaminergic treatment can alleviate motor symptoms for some time, but motor fluctuations may appear even at early stages of the disease 4. Therefore, most treatment strategies also aim at delaying the evolvement of motor fluctuations as long as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Levodopa (LD) remains the most effective and widely prescribed drug in the symptomatic treatment of PD 1 . Currently it is acknowledged that up to 50% of patients have motor fluctuations after two years of the introduction of LD or another dopaminergic agonist (DA) 2,3 . The long-term use of levodopa leads to complications directly related to the duration of the treatment.…”
mentioning
confidence: 99%
“…Wearing-off (WO) is one subtype of motor fluctuation and occurs over time, when the effectiveness of a dose of dopaminergic agonist tends to wear off earlier than before. For confirmation of this phenomenon, WO symptoms should improve after the intake of the next dose of antiparkinsonian drug (AD) 2 . The physiopathology of WO is controversial; it could be due to the decrease of the pre-synaptic dopamine receptors with consequent diminished storage capacity of dopamine in the striatum, or beyond post-synaptic mechanisms as the interruption of signal transduction for synthesis of proteins mediated by D1 and D2 receptors, or because of dopamine depletion due to neuronal loss.…”
mentioning
confidence: 99%